L’évaluation pré/post des effets de la communication du risque sur la perception du risque : l'exemple de la pêche sportive dans le Saint-Laurent autour de Montréal - Jacques Grondin; Dany Laverdière; Richard LaRue (VertigO)
The pre/post approach is widely used to measure knowledge and skills acquisition or to evaluate the effects of different interventions; being easy to apply can incite communicators to use it to measure the effect or the penetration rate of the messages in their audience. This article illustrates the use of this evaluation approach with an example of environmental health risk communication. The strategy was to measure risk perception indicators before a risk communication intervention (pre-test), after risk communication (post-test) and during a follow-up one year later to check if changes measured during the post-test were persistant ou volatile. Three means of communication were used to inform about the risk analysis, namely by oral presentation, by a pamphlet and via the media (radio, television).All communication means had a measurable effect on risk perception, albeit limited because the perception of the majority did not change between the pre-test and the post-test. Moreover, the type (negative/positive) and the amplitude (strong/weak) of the opinion changes varied unequally with each indicator used. Finally, among those respondants that had changed their opinion between the pre-test and the post-test, part of these again changed their opinion between the post-test and the follow-up; this suggests that the effects of risk communication on risk perception might be somewhat volatile. These data point to the need to further validate the indicators typically used to assess risk perception. After discussing potential biases, the authors conclude that the limitations of pre/post evaluation concerning the effects of risk communication on attitudes and opinions does not adequately assess the real value of risk communication.